2010
DOI: 10.14411/fp.2010.026
|View full text |Cite
|
Sign up to set email alerts
|

First species of Ophiotaenia (Cestoda: Proteocephalidea) from Madagascar: O. georgievi sp. n., a parasite of the endemic snake Leioheterodon geayi (Colubridae)

Abstract: Ophiotaenia georgievi sp. n. (Proteocephalidea: Proteocephalinae) is described from the intestine of endemic colubrid snake Leioheterodon geayi Mocquard (Colubridae) from Antananarivo in Madagascar. The new species is the first species of Ophiotaenia la rue, 1911 reported from Madagascar. it differs from all Ophiotaenia species parasitic in african snakes in the possession of a three-layered embryophore of eggs (other african species have two-layered embryophore). Furthermore, O. georgievi can be distinguished… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 22 publications
2
4
0
Order By: Relevance
“…The present study supports the assumption about strict (oioxenous) host specificity of species of Ophiotaenia from reptilian hosts (see de Chambrier et al, 2010 , 2017 , 2020 ) because the new species was found only in E. carinatus sochukeri , but not in any of 33 other snakes of six species, including the congeneric Oman saw-scaled viper, Echis omanensis . It is worth noting that the latter species belongs to the E .…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The present study supports the assumption about strict (oioxenous) host specificity of species of Ophiotaenia from reptilian hosts (see de Chambrier et al, 2010 , 2017 , 2020 ) because the new species was found only in E. carinatus sochukeri , but not in any of 33 other snakes of six species, including the congeneric Oman saw-scaled viper, Echis omanensis . It is worth noting that the latter species belongs to the E .…”
Section: Resultssupporting
confidence: 90%
“…In addition, O. echidis n. sp. possesses a trilayered embryophore, which is present only in a few species of Ophiotaenia from snakes, such as Ophiotaenia lapata Rambeloson, Ranaivoson et de Chambrier, 2012 from Madagascarophis colubrinus (Schlegel), Ophiotaenia georgievi de Chambrier, Ammann et Scholz, 2010 from Leioheterodon geayi (Mocquard) (both host (Pseudoxyrphophiidae), and O. bungari de Chambrier, Binh et Scholz, 2012 from Bungarus fasciatus (Schneider) (Elapidae) (see de Chambrier et al, 2010 ; 2012 ; Rambeloson et al, 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…The present finding, as well as a number of new proteocephalidean species recently described from snakes and amphibians (see, e.g., Puga and Formas 2005, de chambrier et al 2006, 2010, 2012, ammann and de chambrier 2008, coquille and de chambrier 2008, Marsella and de chambrier 2008, de chambrier and gil de Pertierra 2012, gamil 2012, rambeloson et al 2012) indicate that the cestode fauna of these vertebrate hosts is poorly known. Molecular data, although very scarce and fragmentary, also indicate that the existing classification does not correspond to phylogenetic relationships of individual groups (de chambrier et al 2004(de chambrier et al , Hypša et al 2005.…”
Section: Australotaenia Bunthangisupporting
confidence: 79%
“…A number of Ophiotaenia spp. including O. ophiodex and O. nigriocollis also infect snakes in Africa [25][26][27][28]. The anurans harbouring larval proteocephalid cestodes may be intermediate hosts of the Ophiotaenids parasitizing snakes in the rainforest and the derived savanna of Nigeria.…”
Section: Discussionmentioning
confidence: 99%